The effects of environmental taxation on stock returns of renewable energy producers: Evidence from Turkey - Katircioglu, Setareh; Katircioglu, Salih (Pergamon-Elsevier Science Ltd, 2023)
The current study investigates if environmental taxation in Turkey significantly impacts stock returns of renewable energy producers. Renewable energy-related firms trading Istanbul Stock Exchange and the overall energy stock index are selected and analyzed using time series methods. Results generally confirm the long-term effects of taxation on renewable energy stock prices. This study demonstrates that variations in national envi-ronmental regulations and energy taxation result in significant variations in energy stock performance. It is also found that foreign direct investments in Turkey negatively impact energy stock markets. Implications are pro-vided at the end of this study.
Keywords: Environmental regulation; Energy tax; Energy stock price; Cointegration; Turkey